Defining the Focus of Attention: Effects of Attention on Perceived Exertion and Fatigue - Lohse, Keith; Sherwood, David E. (Frontiers in Psychology, 2011)
This manuscript presents two experiments designed to explore the effects of attention on perceived exertion and time to failure in a fatiguing athletic task. There were two major motivating factors for these experiments. First, there are few studies evaluating attentional focus effects in endurance tasks and, second, there is a lack of integration between studies of attentional focus as external/internal (e.g., Wulf, 2007) compared to associative/dissociative (e.g., Stevenson & Biddle, 1998). In Experiment 1, we used a fatiguing wall-sit posture (essentially a complex, isometric task) to compare two different types of external attention with an internal focus on the position of the legs. An external focus (regardless of type) increased the time taken to failure and reduced perceived exertion. In Experiment 2, we manipulated subjects’ expectancy of fatigue to test the interaction of attention and expectancy (both top-down factors) in this highly fatiguing task. Previous theories of attention during endurance tasks have suggested that as fatigue/pain increase, bottom-up factors begin to dominate subjects’ attention. While this may be true, Experiment 2 showed that even in a highly fatiguing task, attentional strategies and expectancies affected the time to failure and perceived exertion.